Boosting 21st Century Skills: Project-Based Microteaching’s Impact on Communication and Collaboration in Biology Education - Sadikin, Ali; Rusdi, Muhammad; Hasibuan, Muhammad Haris Effendi; Siburian, Jodion (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2024)
This study uniquely addresses the gap in preparing prospective biology teachers for 21st-century education by integrating Project-Based Learning (PjBL) into microteaching. The research investigates the impact of this innovative approach on enhancing essential skills such as communication and collaboration. Utilizing a quantitative one-group pretest-posttest design, data was collected from 34 students out of a population of 109 through random sampling, employing questionnaires and interviews. The analysis, conducted using t-tests, revealed a significant improvement in both communication and collaboration skills, with collaboration showing a higher influence. These findings underscore the efficacy of PjBL in fostering these competencies, which are critical for modern educational environments. The implications of this study suggest that optimizing project design, providing robust support and guidance from educators, ensuring resource availability, focusing on continuous evaluation, and offering targeted training for educators are vital for the successful implementation of PjBL-based microteaching. This approach not only enhances the pedagogical skills of prospective teachers but also aligns with the broader educational goal of developing well-rounded, competent educators equipped to meet the challenges of contemporary classrooms. The study's results contribute valuable insights for educational policy and curriculum development, emphasizing the need for innovative teaching methodologies to prepare future educators effectively.